THE EFFECT OF HUMAN RESOURCE QUALITY, ENTREPRENEURIAL ORIENTATION, AND DIGITAL MARKETING STRATEGY ON MSMES PERFORMANCE - Ferdianto, Jemmy Regri; Padang, Rikky Rundu; Suciyawati, Ni Putu (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to analyze the influence of human resource quality (HR), entrepreneurial orientation, and digital marketing strategies on Micro, Small, and Medium Enterprises (MSMEs) performance in the Kaliwates District, Jember Regency. The background of this study is based on the need for MSMEs to adapt to the dynamics of the digital economy, which demands strengthened HR competencies, entrepreneurial innovation, and the optimization of technology-based marketing. This study uses a quantitative associative approach with an explanatory research design. A sample of 72 micro-business owners was selected using the purposive sampling technique, based on the criteria of having been in operation for at least two years and being engaged in the trade and service sectors. Data were collected using a structured questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 25. The research results show that, partially, human resource quality has a positive and significant effect on MSME performance, with a significance value of 0.015. Entrepreneurial orientation also has a positive and considerable influence, with a significance level of 0.012. Digital marketing strategies also positively contribute to the performance of MSMEs with a significance value of 0.009. Simultaneously, the three independent variables contribute 46.8% to MSME performance, while other factors outside the research model influence 53.2%. These findings strengthen the importance of synergy between human resource quality, entrepreneurial orientation, and the implementation of digital marketing in improving MSME competitiveness in the economic era based on technology. This research recommends continuous HR training, strengthening innovative orientation in entrepreneurship, and optimization of various channels of digital marketing as an important strategy to increase the performance of MSMEs. In addition, future research is expected to explore other external factors such as product innovation and access to capital in enriching the MSMEs development model.